UP1304, a Botanical Composition Containing Two Standardized Extracts of Curcuma longa and Morus alba, Mitigates Pain and Inflammation in Adjuvant-induced Arthritic Rats - Yimam, Mesfin (Pharmacognosy Res, 2016)
BACKGROUND: Though, the initial etiologies of arthritis are multifactorial, clinically, patients share pain as the prime complaints. Present day pain relief therapeutics heavily relies on the use of prescription and over the counter nonsteroidal anti-inflammatory drugs as the first line of defense where their long-term usage causes gastrointestinal and cardiovascular-related side effects. Hence, the need for evidence-based safer and efficacious alternatives from natural sources to overcome the most prominent and disabling symptoms of arthritis is an overdue. Here, we evaluated the anti-inflammatory and analgesic effect of UP1304, a composition that contains a standardized blend of two extracts from the rhizome of Curcuma longa and the root bark of Morus alba in adjuvant-induced arthritis models in rats. MATERIALS AND METHODS: The anti-inflammatory and analgesic effects of the botanical composition were demonstrated in adjuvant-induced arthritis models in rats with oral dose ranges of 50–200 mg/kg. Ibuprofen at a dose of 100 mg/kg was used as a reference compound. Ex vivo sulfated glycosaminoglycan inhibition assays were performed. RESULTS: Statistically significant improvements in pain resistance, suppression of paw edema and ankle thickness were observed in animals treated with UP1304 compared to vehicle-treated diseased rats. These results were similar to those achieved by ibuprofen treatment. Inhibitions of proteoglycan degradation were observed in a range of 37.5–61.7% for concentration of UP1304 at 50–200 μg/mL when compared to interleukin-1α-exposed untreated explants. CONCLUSIONS: These data suggest that UP1304, for its analgesic and anti-inflammatory effects, could potentially be considered agent of botanical origin for the improvement of arthritis associated symptoms. SUMMARY: Pain is one of the cardinal signs of arthritis. Long term applications of commonly used non-steroidal anti-inflammatory drugs for pain relief are associated with cardiovascular and gastrointestinal side effects. Cartilage degradation evidenced as glycosaminoglycan loss from articular cartilage into the synovial fluid has been reported in arthritis patients. Adjuvant–induced arthritis model in rats are among the widely used models for efficacy evaluation of nutraceuticals. Efficacy of UP1304, a composition containing a blend of two standardized extracts from the rhizome of Curcuma longa and root bark of Morus alba, was evaluated in adjuvant–induced arthritis model in rats and in glycosaminoglycan releasing inhibition assays. UP1304 demonstrated its enhanced significance by improving the major cardinal signs of arthritis in vivo and ex vivo. UP1304 could potentially be considered as a dietary supplement product for the management of arthritis.